Kearifan Lokal Suku Dayak Maanyan sebagai Filosofi Kehidupan Tradisional - Andreas Mariano (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
The focus of this study is to understand the phenomena that occur within the scope of local wisdom of the Maanyan Dayak tribe. This study uses the library methodology from previous research. This writing finds various philosophical meanings contained in culture. Local wisdom is the main basis for understanding writing. There are various analysis results from previous studies that were developed. The Dayak Maanyan tribe has a precious meaning of togetherness in local wisdom. Several things become the main discussion as follows. First, local wisdom is seen as an effort to preserve culture. Second, traditions passed down and passed down by our ancestors have philosophical values ​​that are rich in life. Third, the relevance of customary values ​​in the life of the nation and state is a characteristic of the Indonesian people.